Emergency ethics : public health preparedness and response - Jennings, Bruce, 1949-; Arras, John D., 1945-2015; Barrett, Drue H.; Ellis, Barbara A. ([New York] : Oxford University Press, 2016)
This edited volume brings together some of the leading scholars in the fields of public health ethics and bioethics to discuss disaster or emergency ethics and ethical aspects of preparedness and response with specific application to public health policy and practice. The book fills a gap in the existing public health ethics literature by providing a comprehensive ethical conception of emergency preparedness as a distinctive form of civic'practice' brought about by the interrelationships and coordination of many groups, disciplines, and interests and drawing on numerous bodies of knowledge and expertise.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on April 8, 2016).
Keywords: Public health -- Moral and ethical aspects; Emergency medicine -- Moral and ethical aspects; Disaster medicine -- Moral and ethical aspects; Emergency management